A NOVEL METHODOLOGY FOR TIME PLANNING OF RESOURCE-CONSTRAINED SOFTWARE PROJECTS WITH HESITANT FUZZY DURATIONS: A CASE STUDY - Basar, Ayfer (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
Time planning of software projects is a complex process for almost all companies. Uncertainties about effort required may cause underestimation or overestimation. Thus, enterprises may encounter an unrealistic schedule and choosing the appropriate planning method becomes crucial. This paper presents a novel integrated decision support methodology for time planning of resource constrained software projects. For this aim, after identifying the effective criteria by the help of expert judgments from the Turkish Information Technology industry and literature review, we find their priorities by Hesitant Fuzzy Pairwise Comparison and calculate estimated effort for the projects. Then, we use the priorities of criteria and estimated durations of the projects in a mathematical programming model proposed to find starting and finishing (delivery) time of the projects. Furthermore, we apply the methodology for solving the project time planning problem of a Turkish software company. It is seen that the proposed method provides efficient schedules.